PARADIGMA HUKUM SEBAGAI TOOL ENGINEERING: BERSIFAT PREVENTIF ATAU REPRESIF? - Yahdika, Mohammad Akmal (LPPM Universitas Bina Bangsa, 2023)
Human are social beings who live in a group of people that have different interests from one another. To regulate and control this heterogeneous life we need a tool or mechanism that must be carried out and obeyed by all social communities. From that, law is present in the midle of social life in the form of rules and norms to regulate so that prosperity and peace can be created. In order to work optimally, it is necessary to identify the nature of the law itself, wheter it is preventive or repressive. The research method used to identify the nature of law as an engineering tool is qualitative with an normative juridicial approach. This is supported by techniques for collecting legal materials using library research which can be in the form of books, journals or articles and document studies in the form of legislation. From the results of the research cunducted, it can be concluded that basically law must be preventive and repressive at the same time. This can be seen from the purpose of law formation that one of them is to prevent riots and chaos. At the same time, the law is can used to be a basis to take care if there is chaos or riots that cannot be prevented by the nature of preventive law